An LMNB1 Duplication Caused Adult-Onset Autosomal Dominant Leukodystrophy in Chinese Family: Clinical Manifestations, Neuroradiology and Genetic Diagnosis - Dai, Yi; Ma, Yaling; Li, Shengde; Banerjee, Santasree; Liang, Shengran; Liu, Qing; Yang, Yinchang; Peng, Bin; Cui, Liying; Jin, Liri (Frontiers in Molecular Neuroscience, 2017)
Abstract: Autosomal dominant adult-onset demyelinating leukodystrophy (ADLD) is a very rare neurological disorder featured with late onset, slowly progressive central nervous system demyelination. Duplication or over expression of the lamin B1 (LMNB1) gene causes ADLD. In this study, we undertook a comprehensive clinical evaluation and genetic detection for a Chinese family with ADLD. The proband is a 52-year old man manifested with autonomic abnormalities, pyramidal tract dysfunction. MRI brain scan identified bilateral symmetric white matter hyper-intensities in periventricular and semi-oval white matter, cerebral peduncles and middle cerebellar peduncles. The proband has a positive autosomal dominant family history with similar clinical manifestations with a trend of genetic anticipation. In order to understand the genetic cause of the disease in this family, target exome capture based next generation sequencing has been done, but no causative variants or possibly pathogenic variants has been identified. However, Multiplex ligand-dependent probe amplification(MLPA) showed whole duplication of LMNB1 gene which is co-segregated with the disease phenotype in this family. This is the first genetically confirmed LMNB1 associated ADLD pedigree from China.